T-Peak to T-End Interval for Prediction of Positive Response to Ajmaline Challenge Test in Suspected Brugada Syndrome Patients - Mananchaya Thapanasuta; Ronpichai Chokesuwattanaskul; Pattranee Leelapatana; Voravut Rungpradubvong; Somchai Prechawat (Medical Sciences, 2022)
Background: Brugada syndrome (BrS) is diagnosed in patients with ST-segment elevation with coved-type morphology in the right precordial leads, occurring spontaneously or after provocative drugs. Due to electrocardiographic (ECG) inconsistency, provocative drugs, such as sodium-channel blockers, are useful for unmasking BrS. Ajmaline is superior to flecainide and procainamide to provoke BrS. Prolonged T-peak to T-end (TpTe) is associated with an increased risk of ventricular arrhythmia and sudden cardiac death in Brugada syndrome patients. Objective: This study aimed to investigate the predictive value of T-peak to T-end interval and corrected T-peak to T-end interval for predicting the positive response of the ajmaline challenge test in suspected Brugada syndrome patients. Methods: Patients who underwent the ajmaline test in our center were enrolled. Clinical characteristics and electrocardiographic parameters were analyzed, including TpTe, corrected TpTe, QT, corrected QT(QTc) interval, and S-wave duration, compared with the result of the ajmaline challenge test. Results: The study found that TpTe and corrected TpTe interval in suspected BrS patients were not significantly associated with a positive response to the ajmaline challenge test. Conclusions: The T-peak to T-end interval and corrected T-peak to T-end interval could not predict the positive response of the ajmaline challenge test in suspected Brugada syndrome patients.